Who is Responsible for Instability in the Democratic Republic of Congo? - Sidorova, G. M. (Vestnik MGIMO-Universiteta, 2014)
The research focuses on the problem of military-political instability in the Democratic Republic of the Congo experiencing continued armed conflict for a long time. Dozens of illegal armed groups both Congolese and foreign origin continue to destabilize situation in the eastern part of the country causing humanitarian disasters. Due to governmental weakness, economic backwardness, chronical lack of finance resources, interethnic conflicts, all-round and widely spread corruption of the authorities, the Congolese government at the moment is not able to overcome scores of problems including the problem of security. Assistanceprovided to the DRC by itspartnerssuch as, first of all, the former metropolitan country Belgium, as well as the USA, Great Britain, the Europe Union and China works only in favourof these country-donors. They are attracted by rich Congolese natural resources which the DRC remaining one of the poorest countries in the world cannot turn to advantage to the full extent because of its economic backwardness. In exchange for so-calleddevelopment programmes, expensive strategic raw material (such as coltan, wolfram, casseterit, cooper, gold, niobium, and other) is being extracted and exported from the country, in addition, often on the inequivalent basis. This is taking place for the reason that numerous mines and open-cast mines are being controlled by different illegal armed groups and not by the central government. Therefore, it turns out that in the context of a military-political crisis, for so-called partners it is more beneficial to pursue their own interests. Furthermore, western ideologists arouse "separatism-oriented" theories similar to "balkanization", in other words, a breakdown of this giant country into several independent states. The Congolese are tremulous to this issue, they try to counter such approachs and defend the territorial integrity of the DRC. However, it is not an easy task. The impediment is unsettled relations with neighbouring countries - Rwanda, Uganda and Burundi which for tens of years exploit illegally natural resources of the DRC and try to lay hold of frontier Congolese territories.